Destiny and creativity of military draft writers - Shamyakina, Tatʼyana I. (Journal of the Belarusian State University. Sociology, 2020)
The attitude of front-line writers and those writers who survived the Great Patriotic War in childhood is considered. The author gives an assessment of the political and social phenomena of the post-war period from the perspective of today. The question is highlighted – the writer and ideology. The main attention is paid to the military experience of writers and their reflection in their work. The prose of the most prominent representatives of two generations of writers is analyzed. Significant for our time, works are also evaluated in terms of plots, images, styles. The work of V. Bykov is investigated in detail. The importance of the work of Belarusian front-line writers in the development of Belarusian literature is indicated.
Keywords: front-line; writter and ideology; military prose